PENGATURAN SANKSI PIDANA TERHADAP KORPORASI SEBAGAI PELAKU TINDAK PIDANA PERIKANAN BERDASARKAN UNDANG-UNDANG NOMOR 31 TAHUN 2004 JUNCTO UNDANG-UNDANG NOMOR 45 TAHUN 2009 TENTANG PERIKANAN - Victor Silalahi; Mukhlis R; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Recognition of corporations as subjects in criminal offenses in the fishery sector is contained in Article 101 of Law Number 31 of 2004, Juncto of Law Number 45 of 2009 concerning Fisheries which states that, in the event that the criminal acts referred to in this law are carried out by corporations , criminal charges and penalties imposed on the management and criminal penalties plus 1/3 (one third) of the criminal sentences. In this law the criminal target is only aimed at the management only, while the corporation cannot be sentenced. Such an arrangement will cause many weaknesses, Logically, for certain cases where the profits derived by the company are so great and / or the losses incurred by the community are so great, the imposition of imprisonment / fines